PP.12.14: EFFECT OF NEUROVASCULAR DECOMPRESSION IN RESISTANT HYPERTENSION ON BAROREFLEX-SENSITIVITY, TOTAL PERIPHERAL RESISTANCE, CARDIAC AUTONOMIC NEUROPATHY AND PLASMA NOREPINEPHRINE. (June 2015) - Fejes, I.; Voros, E.; Barzo, P.; Abraham, G.; Legrady, P.
Abstract : Objective: In severe resistant hypertension (RHT) not responding to a multiple combination of conventional drug therapy, the neurovascular pulsatile compression (NVPC) of the rostral ventrolateral medulla on the left side may be considered as an etiological factor for the hypertension. In such cases neurovascular decompression (NVD) can lead to blood pressure (BP) reduction and the conventional medication may become more effective. Design and method: A magnetic resonance investigation combined with angiography of the brain stem was performed of a 57-year-old white women with severe RHT treated with 10 different antihypertensive drugs. It showed a NVPC on the left side. The duration of her HT was 36 years. She had impaired glucose tolerance, her BMI was 26.3 kg/m2 and her GFR was 79.5 ml/min/1.73m2. Before and after the operation the next parameters were assessed: the cardiac autonomic neuropathy (CAN) by means of five standard cardiovascular reflex-tests, the spontaneous baroreflex sensitivity (BRS) via a sequence method calculating from ECG and BP data recorded by a Finometer device and the total peripheral resistance (TPR) by the modelflow technique in a 10-minute-long supine and a 10-minute-long standing position, and the plasma norepinephrine (NE) level. Results: After the NVD, both the systolic and diastolic BP decreased significantly likewise the number of antihypertensive medication. Only a 5-folder combination needed after the NVD to maintance the decreased BP. In the supine position, the BRS was 5.62 ms/mmHg before and 7.51 ms/mmHg after NVD. In the standing position, the BRS was 3.29 ms/mmHg before and 5.57 ms/mmHg after NVD. The sum of the CAN scores did not change; it remained 3. The plasma NE level decreased from 421 pg/ml to 282 pg/ml. Conclusions: In conclusion, the NVD of the brain stem on the left side in severe RHT that does not respond to conventional drug therapy can guarantee a significant BP reduction and a better response to antihypertensive medication. The sympathetic activity may decrease and so perhaps the cardiovascular risk also after an NVD.